Upcoming Russian Arctic Council Chairmanship: Priorities and Implications for the High North - Sergunin, Alexander (DEU, 2023)
This study aims to examine Russia's policy priorities for its chairmanship in the Arctic Council and the possible implications thereof for the region. The author argues that Russia's Arctic Council presidential agenda will likely include the following priorities: climate change action; sustainable development; social cohesiveness and connectivity in the region; indigenous peoples; conservation of biodiversity; science diplomacy; and partial institutional reform of the Council. Moscow will not, however, renew its earlier efforts to transform the Council from an intergovernmental forum into a full-fledged international organization and introduce military security issues to the Council's agenda. Russia's chairmanship will likely strengthen the Arctic Council's role in asserting regional stewardship by responding to the challenges of a rapidly changing Arctic.